Transformasi Strategi Pemasaran Digital dalam Ekosistem Kewirausahaan Modern: Tinjauan Literatur - Alvina Viola; Tifani Ade Permana; M Irsan Rasid; Muhammd Zaki; Cici Ramadhani; Trysanti Kisria Darsih (MAN 4 Kota Pekanbaru, 2026)
This study reviews the transformation of digital marketing strategies in the modern entrepreneurial ecosystem through a comprehensive literature review of publications from 2021 to 2025. A descriptive qualitative approach was applied to analyze 40–50 scholarly sources retrieved from Google Scholar, Scopus, ProQuest, and ScienceDirect using thematic content analysis. The findings indicate a rapid acceleration of digital marketing transformation following the COVID-19 pandemic, highlighting seven key strategic components: digital presence, digital competence, data analytics, financial technology, e-commerce platforms, technological innovation, and digital literacy. Digital transformation emerges as a critical determinant of entrepreneurial performance, enhancing operational efficiency and market expansion. However, significant challenges persist, including limited digital literacy, restricted access to capital, and insufficient regulatory support. The study also identifies opportunities for business model innovation and sustainable entrepreneurship. The findings emphasize the importance of synergistic integration among digital marketing components and cross-sector collaboration to strengthen the digital entrepreneurial ecosystem and support inclusive and sustainable economic development.